Tinjauan Literatur: Evaluasi Metode Least Significant Bit (LSB) dalam Steganografi Berdasarkan Alasan Penggunaan dan Efektivitasnya terhadap Keamanan Data Digital - Hadaya Imtiyaza Syarifa; Livia Febriati; Vannianti Nabilla Putri (JIKUM: Jurnal Ilmu Komputer, 2026)
The rapid development of information technology has facilitated the exchange of digital data, but it has also given rise to various threats to information security. Steganography is one technique used to hide confidential data, with the Least Significant Bit (LSB) method being the most widely used approach due to its simplicity. This article aims to evaluate the reasons for using the LSB method in steganography, its weaknesses, and its effectiveness in digital data security. This study uses the Systematic Literature Review (SLR) method by reviewing relevant scientific articles obtained through the Google Scholar database. The literature selection process was carried out systematically using the PRISMA protocol. The results of the study show that the LSB method is widely used because of its ease of implementation, processing speed, adequate insertion capacity, and ability to maintain the visual quality of the disguised image. However, this method has limitations, particularly low resistance to noise, lossy compression, image manipulation, and steganalysis attacks when used alone. Therefore, the LSB method is considered quite effective for visual concealment, but it needs to be combined with additional security techniques to improve digital data security.